The association between serum adiponectin and anthropometric measurements in Malay adults - Mohamed, H.J. Jan (Universiti Sains Malaysia, 2009)
Low level of serum adiponectin is associated with low physical activity and high caloric intake. It is also proposed to vary bet-.veen ethnicity. Hence, we aimed to investigate the association between serum adiponectin and anthropometric measures in adults from the Malay eihnicity. This is a cross-sectional study involving 43 adults aged between 30 to 70 years old living in a rural village in Malaysia. Anthropometric measurements include height, weight, waist circumference and hip circumference. Body composition was measured using lnnerScanTM Body Composition Monitor (Tanita, Japan). Body mass index (BMI) and waist· hip-ratio (WHR) was calculated using standard formula. Serum adiponectim was measured using a commercial adiponectin Enzyme Linked lmmunosorbent Assay (Millipore, USA). Serum adiponectin ranged from 3.7 llglml to 42.6 llglml with mean of 16.2 llglml. Adiponectin level was significantly (P< 0.001) higher in female (18.8 llg/ml) compared to male (9.4 llglml) subjects. Adiponectin was significantly correlated with waist circumference (r=-0.4, P< 0.05), waist-hip-ratio (r=-0.4, P< 0.0 I) and visceral fat (r=-0.3, P< 0.05). No significant association was found between adiponectin with BMI and percentage body fat. Adiponectin is associated with measures of central obesity such as waist circumference, WHR and visceral fat. Hence, it has potential to appear as a biomarker for central obesity and could be possibly used as one of the component for metabolic syndrome criteria.